2010
DOI: 10.1007/s12237-009-9248-7
|View full text |Cite
|
Sign up to set email alerts
|

City-Based Risk Assessment of Sea Level Rise Using Topographic and Census Data for the Turkish Coastal Zone

Abstract: Turkish coastal zone elevation to sea level rise was illustrated using a digital elevation model and methods in a geographical information system. It was intended to determine several parameters such as population, settlements, land use, wetlands, contribution to national agricultural production, and taxes at risk using high-resolution Shuttle Radar Topography Mission topographic, orthorectified Landsat Thematic Mapper Mosaics and census data with geographical information system methods within 0-to 10-m elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 9 publications
1
8
0
1
Order By: Relevance
“…This includes coastal flats, estuaries and bays over which most coastal cities, harbours and resorts are located. Similarly, in Turkey, numerous coastal cities and villages are located within the 0-10 m elevation zone and are vulnerable to SLR (Kuleli, 2010). In terms of potential land loss, the Mediterranean coast of Turkey is the most vulnerable, with islands of the eastern Mediterranean being particularly affected.…”
Section: Accepted Articlementioning
confidence: 99%
“…This includes coastal flats, estuaries and bays over which most coastal cities, harbours and resorts are located. Similarly, in Turkey, numerous coastal cities and villages are located within the 0-10 m elevation zone and are vulnerable to SLR (Kuleli, 2010). In terms of potential land loss, the Mediterranean coast of Turkey is the most vulnerable, with islands of the eastern Mediterranean being particularly affected.…”
Section: Accepted Articlementioning
confidence: 99%
“…Although coastal cities cover less than 5% of the country, at least 30 million people inhabit these places and the population is still growing at a rapid rate (Karaca & Nicholls 2008). Recent national and local scale investigations in Turkey have shown that some coastal areas, particularly the low lying deltaic plains, are highly vulnerable to the future sea level rise (Demirkesen et al 2008;Karaca & Nicholls 2008;Alpar 2009;Kuleli et al 2009;Kuleli 2010). The vulnerability of the Turkish coastal areas to permanent inundation was quantified by Demirkesen et al (2008) based on the synthetic scenarios of constant sea level changes and the digital elevation model acquired by shuttle radar topography mission (SRTM).…”
mentioning
confidence: 99%
“…And then the impacts of infrastructure and economic investments in case of the basins (the Göksu basin connecting inner Anatolia to Mediterranean which includes a delta protected by International Ramsar Convention, the Bakırçay basin in West Anatolia and Anatolian side of Istanbul basin oriented towards the Black Sea covering a shore land and water through which includes a natural site) from Turkey pointed out in Fig. 1 are explained, taking the sea level rise study results of Kuleli [11], Kuleli et al [12], Alpar [13], Demirkesen et al [14] for Turkey into consideration. Subsequently, the implications of infrastructure and economic investments being applied and/or envisaged at regional and local scale and their reciprocal interactions with the natural (water, air, soil, etc.)…”
Section: Factors Of Climate Change In Different Basinsmentioning
confidence: 99%